THE The Influence Of Customer Engagement On Brand Loyalty With Brand Attachment And Customer Trust As Intervening Variables: A Case Study At Starbucks Ijen, Malang City - Alhamrouni, ahmed; Siti Asiyah; Ridwan Basalamah (LP2M IAIN Palopo, 2026)
This study aims to examine the influence of Customer Engagement on Brand Loyalty with Brand Attachment and Customer Trust as intervening variables in the context of Starbucks Ijen Malang. A quantitative descriptive and causal approach was employed, with data collected from 100 respondents using questionnaires and analyzed through SEM-PLS. The findings reveal that Customer Engagement has a strong and significant impact on Brand Loyalty, both directly and indirectly. Brand Attachment demonstrates the highest mediating effect, indicating that emotional bonds play a dominant role in fostering loyalty, while Customer Trust also significantly contributes as a mediator, although to a lesser extent. The results confirm that high engagement enhances both emotional attachment and trust, which in turn strengthen customer loyalty. The study contributes theoretically by enriching the understanding of the interrelationship between engagement, attachment, and trust in loyalty formation, and practically by providing insights for Starbucks to strengthen relationship marketing strategies. The research is limited to a single location with non-probability sampling, suggesting future studies should broaden scope, adopt mixed methods, and incorporate additional variables such as satisfaction or brand experience. Overall, this study highlights that sustainable Brand Loyalty in premium coffee shops can be achieved through active engagement, emotional attachment, and consistent trust.